Does boardroom nationality affect the performance of UK insurers?. Issue 5 (September 2021) - Adams, Mike; Baker, Paul L.
Abstract: Drawing on the board capital literature, we use a panel data design to investigate the effect of boardroom nationality on the profitability and solvency of property-casualty insurers operating in the United Kingdom (UK). We find that boardroom nationality influences corporate outcomes depending on the financial aspects being measured. For example, North American directors are linked with profitable outcomes, while European directors tend to be associated with better solvency. This reflects differences between the shareholder value corporate culture in North America and stakeholder approaches more common in Europe. Our results could help insurers, regulators, and others (e.g., investors) to better understand the potential performance implications of the appointment of directors of different nationality.